Disclosure of Environmental, Social, Governance, and Company Size Performance on Company Value in the Energy Sector - Muthia, Sevia Putri; Basyith, Abdul; Kalsum, Ummi (International Journal of Finance Research, 2024)
This study aims to determine the effect of Disclosure of Environmental, Social, Governance, and Company Size Performance on Company Value in Energy Sector companies for 2017-2021. The population in this study was 72 companies in the Energy sector. After going through the purposive sampling method, the number of samples used in this study became 8 companies with 40 total observations. The data used in this study is secondary data taken through the annual report and the Sustainability Report downloaded from the company's website. Data taken from the Annual Report, namely Tobin's Q data for the variable Corporate Value, Number of Audit Committee Members for the Variable Governance and Total Assets for the variable Company size, while the data taken from the Sustainability report included PROPER for Environmental Performance Variables and GRI Index Disclosures for Social. The analysis technique used is Multiple Regression Analysis. This study found that environmental, social, corporate governance, and size performance positively and significantly affected firm value. On the other hand, social had a negative and insignificant effect on firm value. Meanwhile, environmental performance has a positive and insignificant effect on firm value compared to corporate governance and size, which negatively and significantly impacts firm value